On the osteogenic differentiation of dental pulp stem cells by a fabricated porous nano-hydroxyapatite substrate loaded with sodium fluoride - Arab, Samaneh; Bahraminasab, Marjan; Asgharzade, Samira; Doostmohammadi, Ali; Zadeh, Zahra Khatib; Nooshabadi, Vajihe Taghdiri (BMC oral health, 2024)
In the present study, nano-hydroxyapatite (n-HA) powder was extracted from carp bone waste to fabricate porous n-HA substrates by a molding and sintering process. Subsequently, the substrates were loaded with different amounts of sodium fluoride (NaF) through immersion in NaF suspensions for 10, 7.5, and 5 min. The NaF-loaded n-HA substrates were then examined for their structural and physical properties, chemical bonds, loading and release profile, pH changes, cytotoxicity, and osteogenic effect on dental pulp stem cells (DPSCs) at the level of RNA and protein expression. The results showed that the n-HA substrates were porous (> 40% porosity) and had rough surfaces. The NaF could be successfully loaded on the substrates, which was 6.43, 4.50, and 1.47 mg, respectively for n-HA substrates with immersion times of 10, 7.5, and 5 min in the NaF suspensions. It was observed that the NaF release rate was rather fast during the first 24 h in all groups (39.06%, 36.43%, and 39.57% for 10, 7.5, and 5 min, respectively), and decreased dramatically after that, indicating a slow detachment of NaF. Furthermore, the pH of the medium related to all materials was changed during the first 4 days of immersion (from 7.38 to pH of about 7.85, 7.84, 7.63, and 7.66 for C0, C5, C7.5, and C10, respectively). The pH of media associated with the C7.5, and C10 increased up to 4 days and remained relatively constant until day 14 (pH = 7.6). The results of the cytotoxicity assay rejected any toxicity of the fabricated NaF-loaded n-HA substrates on DPSCs, and the cells could adhere to their surfaces with enlarged morphology. The results showed no effect on the osteogenic differentiation at the protein level. Nevertheless, this effect was observed at the gene level.